Implementasi Model Pembelajaran Carousel Feedback Untuk Meningkatkan Efikasi Diri, Dan Hasil Belajar Siswa : (Studi Pembelajaran IPS Siswa Kelas VI SDK Kekawii Ende) - Nikolaus Suhario (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
The results of preliminary observations made by researchers at SDK Kekawii Ende on the social studies learning process showed that the learning process was still dominated by teachers. This has an impact on self-efficacy and low student learning outcomes. When the learning process takes place students appear less enthusiastic in participating in learning, ashamed to express opinions, and lack confidence in doing the assignments given by the teacher. Therefore, improvement efforts are needed, namely by applying the carousel feedback model. This research includes Classroom Action Research (PTK). Data collection techniques using observation techniques, tests, documentation, and field notes. The collected data were analyzed descriptively qualitatively and descriptively quantitatively. The results showed that the carousel feedback learning model could increase self-efficacy, motivation, and learning outcomes. This can be seen from the increase in the percentage of students who achieve high and very high levels of self-efficacy, namely 67 percent in cycle I to 83 percent in cycle II. Thus student learning outcomes also increased, seen from the percentage of classical completeness, namely 75 percent in cycle I to 92 percent in cycle II.